2012
DOI: 10.1007/s10815-012-9740-z
|View full text |Cite
|
Sign up to set email alerts
|

Improved pregnancy rates with luteinizing hormone supplementation in patients undergoing ovarian stimulation for IVF

Abstract: Introduction Luteinizing hormone (LH) is believed to play a role in follicle maturation during the natural cycle. However, the need for co-treatment with recombinant LH (rLH) for controlled ovarian stimulation is controversial. Purpose The primary objective of our study was to determine if pregnancy rates are improved when rLH is used in addition to rFSH for ovarian stimulation. Secondary outcomes were fertilization rate, implantation rate and live birth rate. Methods A retrospective cohort study was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…26 Little is known on the association between LHB and EOPET, but previous study suggests that LH plays an important role in placental implantation by increasing blood flow through vasodilatation or through angiogenesis and trophoblast. 27 However, high serum concentration of LH may negatively affect implantation. 28 This implies that the balance of LH is essential for placental implantation.…”
Section: Discussionmentioning
confidence: 99%
“…26 Little is known on the association between LHB and EOPET, but previous study suggests that LH plays an important role in placental implantation by increasing blood flow through vasodilatation or through angiogenesis and trophoblast. 27 However, high serum concentration of LH may negatively affect implantation. 28 This implies that the balance of LH is essential for placental implantation.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that adding LH during ovarian stimulation improves the IVF/ ICSI outcomes, especially in specific groups, e.g. patients with reduced ovarian reserve, low responders, patients with PCOS (polycystic ovarian syndrome), patients older than 35 years and those with reduced endogenous LH levels [23][24][25][26].…”
Section: Cost and Cost-effectiveness Analysis Of The Protocols And Comentioning
confidence: 99%
“…Sonntag et al report that long-term use of GnRH-a can lead to low levels of endogenous LH [19], thus it is important to supplement exogenous LH in patients with low LH levels [20]. Previous studies also found that patients with low serum LH levels achieved better clinical pregnancy rates after adding exogenous LH [15,[21][22][23][24]. Franco et al report that supplementation with rLH signi cantly increases the number of fertilized oocytes obtained and the rate of cumulative live births [25].…”
Section: Discussionmentioning
confidence: 99%